FUNCTIONAL OUTCOME OF TOTAL HIP - Osama Jafar; Aziz-ur-Rehman; M. Kaleem Shaukat (Journal of University Medical & Dental College, 2015)
ABSTRACT: Osteoarthritis is a chronic, progressive articular disorder characterized by pain. More than 10% of people older than 60 years of age are affected by osteoarthritis of the hip. In the present study the functional outcome of the total hip arthroplasty was recorded. It was inferred from the current study that the functional outcome observations were highly encouraging. It is very normal observation that the patients were crippled because of the pain, loss of movements and inability to carry out day to day activities due to arthritis of hip joint. The same functional improvements were also recorded from the pre and post operative X-rays and examinations of the patients according to the Harris Hip Score (HHS). It was concluded from the current study that total hip arthroplasty is a safe surgical procedure with enormous beneﬁts with minimal complications in our setup in experienced hands. It was further suggested that in the present study the time period of the study was short so in order to get better evaluation, longer follow up period is required.OBJECTIVES: To evaluate the functional outcome of total hip arthroplasty in terms of pain relief, functional capacity, range of motion and absence of deformity using Harris hip score.STUDY DESIGN: Descriptive case series study.PLACE OF STUDY: Orthopaedic Department Shaikh Zayed Hospital, Lahore and Madina Teaching Hospital University Medical and Dental College Faisalabad.DURATION OF STUDY AND SAMPLE SIZE: This study of 60 cases was conducted in one year.MATERIALS AND METHODS: Sixty patients meeting the inclusion criteria were admitted through orthopaedics outpatient department of Sheikh Zayed Hospital Lahore and Madina Teaching Hospital University Medical and Dental College Faisalabad. Pre operative Harris scoring was done and was compared with the post operative score to ﬁnd the improvement.RESULTS: Average pre operative Harris hip score was 23.77±9.50 and post operative score was 87.90±10.42 and this score means good results.CONCLUSION: It was concluded that THR is a safe surgical procedure with promising results in relieving pain, improving movements and upgrading the quality of life